Factors Affecting the Timeliness of Deliveries and Service Quality at J&T Cargo Bekasi Branch During Peak Season - Okin Ringan Purba; Indriyati Indriyati; Adam Muhammad Syailendra; Annisa Azzahra Ramadhini (Green Publisher, 2025)
This research aims to identify internal and external factors, as well as to understand the strategies and challenges faced by J&T Cargo during peak seasons. J&T Cargo, a part of the J&T Group, is a pioneer in technology-based logistics solutions for e-commerce in Southeast Asia, focusing on efficient cargo delivery. The study explores the factors that influence delivery timeliness and service quality at the J&T Cargo branch in Bekasi, especially during surges in e-commerce transactions. Peak seasons present significant logistical challenges, making it essential to maintain timeliness and service quality to meet customer expectations and uphold the company’s reputation. A qualitative research method was employed through in-depth interviews, participant observation, and document reviews from logistics managers and delivery staff at the Bekasi branch. The analysis was used to identify key patterns and themes. The results indicate that improving the management of internal factors can enhance delivery timeliness and service quality. Recommendations for J&T Cargo include adding temporary staff, expanding warehouse capacity, and implementing ongoing training programs for employees to better address challenges during peak seasons.